High‐resolution distribution pattern of surface water nitrous oxide along a cruise track from the Okhotsk Sea to the western Arctic Ocean. Issue Volume 66:Issue S1(2021) Supplement (26th October 2020) - Zhan, Liyang; Zhang, Jiexia; Ouyang, Zhangxian; Lei, Ruibo; Xu, Suqing; Qi, Di; Gao, Zhongyong; Sun, Heng; Li, Yuhong; Wu, Man; Liu, Jian; Chen, Liqi
Abstract: Nitrous oxide in the surface water was measured using an automatic underway system, along with measurements of surface water pCO2, dissolved oxygen, salinity, temperature, and sea ice coverage, along a cruise track through the Bering Sea and Chukchi Sea to the Canadian Basin during the 7 th Chinese National Arctic Research Expedition. The results show that, overall, the regions along the cruise track are net sources of N2 O to the atmosphere. Several N2 O oversaturation maxima were observed along the cruise track, with an absolute maximum of approximately 60%. According to the hydrographic setting and the distribution patterns of pCO2, dissolved oxygen, and sea ice coverage in the study area, it was concluded that the N2 O oversaturation maxima may result from hydrographic processes, such as mixing of different water masses, upwelling or convection, and possible production beneath the sea ice. Additionally, the lowest value of approximately 90% may result from dilution related to the melting of sea ice. An evaluation of the air–sea flux along the cruise track shows that the continental shelf and upwelling region are N2 O sources, whereas the study area in the open Arctic Ocean does not show obvious source or sink characteristics.